ANALYZING UNIQUE RESOURCES OF FAMILY BUSINESS AS STRATEGY TO MAINTAIN AND DEVELOP BUSINESS IN CV SETIA BUDI JAYA BANDUNG - Halidazia, Alya
The role of family business has been able to contribute in the development of entrepreneurial world. However, family business is indicated hard to maintain to the next generation while there is also a finding that oldest family businesses in several countries are still exist. Thus, it raises curiosity about strategy that make a family business have a longevity. In accordance with that, the previous research stated that the company's resources and capabilities are the foundation for determining the company's long-term strategy. Therefore, this research is conducted to analyze the unique resources and attribute of family business that consist of human capital, social capital, patient financial capital, survivability capital, and government structure and cost, which proposed by Sirmon and Hitt. In addition, ownership and control by family members across generations has an indication that business continuity of a family business is crucial. As this research focusing on CV Setia Budi Jaya which has such condition, so it is important to analyze the strategies carried out in each unique resources on that company along with the positive and negative sides in every aspect. In human capital aspect, there is acquired knowledge, skills, and capabilities of a person. Knowledge and skills of employees who are family members are acquired from their formal education, by transfer of knowledge among family members, and experiences. There is also capabilities as innate transfer or talents which are become a consideration to be adjusted to the division they manage. For social capital, there are three dimensions which in family business as components embedded in family that consist of structural dimension which in the work and family relationship between family members is able to build more intimate relationships not only as a co-worker but as a family so the information as well as knowledge can be transferred after hours; relational dimension which among family members as employees in this company works on the basis of trust; and cognitive dimension which there are shared values and perspectives that are generally accordance for all employees with special treatments for family members as they live together. These connections can generate human capital development that create effective relationships with suppliers, customers, and support organizations. For patient financial capital aspect, there is no indication of invested financial capital without threat of liquidation as CV Setia Budi Jaya’s financing is not within internal family members but gain external financial capital of bank loan so there is no limited to availability of family’s financial capital. In addition, CV Setia Budi Jaya has survivability capital as employees who work in their own family business can create a deeper sense of belonging so they will not refuse and willing to carry out more to maintain and develop this company. While for government structure and cost, there is no agency and cost associated with the control of firm as management is done by the family members on the basis of trust in family ties which all of them currently want to maintain and develop this company. As a conclusion, all strategies implemented have a positive side except for the lack of human capital competency, path dependency, and limited number of networks. So the company might be able to carry out a training especially for the head of division and has another option in the form of recruitment which also useful to increase the network as social capital.